Microstructural Mapping of Arctica islandica Shells Reveals Environmental and Physiological Controls on Biomineral Size - Nils Höche; Eric O. Walliser; Bernd R. Schöne (Frontiers in Earth Science, 2022)
The shells of long-lived bivalves record environmental variability in their geochemical signatures and are thus used extensively in marine high-resolution paleoclimate studies. To possibly overcome the limitations of the commonly employed temperature proxy, the δ18Oshell value, which requires knowledge of the seawater δ18O signature and is prone to diagenetic overprint, the shell microstructures and the morphological properties of individual biomineral units (BMUs) recently attracted research interest as an alternative paleoclimate proxy. In shells of A. islandica, one of the most extensively used and best studied sclerochronological archives, the size of the BMUs increases in warmer temperatures under laboratory circumstances. This study assesses whether this relationship persists under natural growth conditions or whether additional environmental and physiological factors control the BMU size and bias temperature reconstructions. For this purpose, shells from the surface waters of NE Iceland and the Baltic Sea, as well as from deeper waters of the North Sea (100 and 243 m) were analyzed by means of SEM. The BMU sizes were measured by means of image processing software. Results demonstrate a strong effect of temperature on the BMU size at NE Iceland and in the North Sea at 100 m depth. At 243 m depth, however, temperature variability was likely too low (1.2°C) to evoke a microstructural change. At the Baltic Sea, the BMUs remained small, possibly due to physiological stress induced by low salinity and/or hypoxia. Thus, the size of BMUs of A. islandica shells only serves as a relative temperature indicator in fully marine habitats, as long as seasonal temperature amplitudes exceed ca. 1°C. Furthermore, BMU size varied through lifetime with the largest units occurring during age seven to nine. This pattern is possibly linked to the shell growth rate or to the amount of metabolic energy invested in shell growth.